Antinutritional Evaluation and In vitro Protein Digestibility of Some Nigerian Cucurbits - Franca, Okoye Ngozi (Pakistan Journal of Nutrition, 2012)
The antinutritional factors of three Nigerian cucurbits namely, ‘snake tomato’ Trichosanthes cucumerina, ‘pumpkins’ Cucurbita pepo and Cucurbita moschata were analyzed. The antinutritional factors evaluated were tannin ranging from 0.23 to 0.49%; oxalate, 0.01 to 0.23%; cyanogenic glycosides, 0.43 to 0.44% and trypsin inhibitor, 6.32 to 11.58 TI unit/g. There were significant differences (p<0.05) in some of the antinutritional components of the cucurbits evaluated. The samples exhibited high protein digestibility but low levels of antinutrients which showed that the cucurbits studied cannot be toxic for human consumption postulating that the samples are of high nutritional quality so large scale production should be encouraged.